Mencegah Perilaku Bullying Melalui Bimbingan Klasikal dengan Media Video di Panti Asuhan - Sutipyo Ru'iya (JKI (Jurnal Konseling Indonesia), 2022)
This study aims to test the effectiveness of classical guidance using video media to reduce bullying behavior at the "X" Putra Orphanage in Yogyakarta. This research can be classified into action research. The number of participants is all residents of the orphanage, totaling 64 people. Guidance is carried out classically by showing a video about the introduction of bullying. There are three videos presented to the counselee which are watched together every Saturday night. The first video is about bullying behavior, the second video is about the negative consequences of bullying, and the third video is about how to avoid bullying. After the counselee watched the video, a joint question and answer session was held. Before the mentoring process began, participants were asked to fill out a pre-test, and after the guidance session was over, participants were asked to fill out a post-test, which had previously been prepared by the researcher and validated by an expert. The data obtained were analyzed descriptively and tested "t" to determine the significance of the pretest and posttest results. From the results of the descriptive analysis it was known that there were three participants who did not experience a decrease in their potential for bullying behavior, while the others experienced a decrease ranging from 1-10 points. The results of the t test obtained the value of t = -10.435 with p = 0.000 which means there is a significant decrease. Thus it can be concluded that classical counseling with video media at the Yogyakarta "X" Orphanage for Boys is effective.